2020
DOI: 10.1007/s00401-019-02098-6
|View full text |Cite|
|
Sign up to set email alerts
|

ACE2 activation protects against cognitive decline and reduces amyloid pathology in the Tg2576 mouse model of Alzheimer’s disease

Abstract: Mid-life hypertension and cerebrovascular dysfunction are associated with increased risk of later life dementia, including Alzheimer's disease (AD). The classical renin-angiotensin system (cRAS), a physiological regulator of blood pressure, functions independently within the brain and is overactive in AD. cRAS-targeting anti-hypertensive drugs are associated with reduced incidence of AD, delayed onset of cognitive decline, and reduced levels of Aβ and tau in both animal models and human pathological studies. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 91 publications
1
104
1
Order By: Relevance
“…No ACE2 ENSG00000130234 X -2.3287002 -4.3401745 1.42E-05 0.000171912 ACE2 activation reduces hippocampal soluble Abeta1-42 (Evans et al, 2020), which is in opposition to our results. However, ACE2 can convert Abeta1-43 to Abeta1-42, which can then be converted to Abeta1-40 by ACE (Liu et al, 2014).…”
Section: Yescontrasting
confidence: 99%
“…No ACE2 ENSG00000130234 X -2.3287002 -4.3401745 1.42E-05 0.000171912 ACE2 activation reduces hippocampal soluble Abeta1-42 (Evans et al, 2020), which is in opposition to our results. However, ACE2 can convert Abeta1-43 to Abeta1-42, which can then be converted to Abeta1-40 by ACE (Liu et al, 2014).…”
Section: Yescontrasting
confidence: 99%
“…The use of antihypertensive drugs has also been proposed as a strategy for ameliorating amyloid pathology. A recent study in which regulation of the RAS was enhanced through ACE2 in the Tg2676 mice model of AD showed that spatial memory was improved in association with a reduction in soluble and insoluble Aβ in the hippocampus (Evans et al, 2020). Here, however, vascular function was not evaluated.…”
Section: Vascular Contributors To Cognitive Impairment and Dementiamentioning
confidence: 97%
“…The reduced incidence of AD found in subjects treated with RAS-targeting anti-hypertensive drugs was attributed to the increased expression of ACE2 in the brain [64][65][66][67][68]. In middle-aged (13-14-month-old) symptomatic AD Tg mice, the activation of ACE2/Ang-(1-7)/Mas axis by diminazene aceturate (DIZE) administration, lowered hippocampal Aβ, neuroinflammation, and restored cognition [69]. Therefore, these findings corroborate a beneficial effect of ACE2 overexpression at CNS even in AD when molecular pathological events are established.…”
Section: Possible Impact Of Sars-cov-2 Infection On Alzheimer's Diseamentioning
confidence: 99%
“…New findings demonstrate APOE4 acts beyond its well-known roles in influencing Aβ pathology and lipid homeostasis, since it has a strong influence in neuronal inflammation, potentially spreading pathological proteins through the brain. In human postmortem studies, gliosis was found to be significantly associated with APOE4 carriers when quantified in different brain regions using multiple markers of activation, including CD68, Human Leucocyte Antigen-DR isotype, and CD64 [68,69]. Therefore, the interplay between APOEε4 phenotype and innate immune response in the brain following virus infection, such as astrocytes and microglial cells, should be well investigated, as a driving force that sustains neuroinflammation and leads to AD exacerbation.…”
Section: Possible Impact Of Sars-cov-2 Infection On Alzheimer's Diseamentioning
confidence: 99%
See 1 more Smart Citation